Menjadi Ladies: Social Climber dan Gaya Hidup Hedonis Pada Remaja Putri di Kota Banjarmasin - Yurizal, Irianti Utami; Damaiyanti, Varinia Pura (Huma: Jurnal Sosiologi, 2024)
The lifestyle applied by ladies who are still teenagers in Banjarmasin City is an interesting thing to investigate more deeply. This research aims to find out in depth the background of teenagers doing social climber, the efforts made by teenagers to do social climber, and social climber in the perception of a ladies. This research uses descriptive qualitative method. The research instruments used observation and in-depth interviews. This research was conducted in Banjarmasin City. The results showed that a friendship environment that has a hedonic lifestyle is a form of lifestyle that emerged after the current massive modernization. Hedonic lifestyle or things that are considered fun are dominantly related to luxury. Teenagers who like new things, such as technology, the latest clothing models, the latest hairstyles, and others. The social climber's life has a self-created culture that encompasses a whole set of values and behaviors, which are considered self-discovery. Efforts are made to work, become the mistress of a rich man, and manipulate parents. Adolescent social climbers perceive that women's work has the opportunity to earn a lot of money in an easy way, and increase popularity. In some professions, women sometimes get lower salaries than men. The ladies' job in question is to serve men who are much older than the ladies, who are usually called om-om. Being a lady is not an easy job, sometimes getting violence, especially regarding health will be very vulnerable.